Formation of Highly Permeable Soil on a Heavy Soil Base Under Tidal Irrigation and Drainage Conditions†. (25th April 2018) - Ashrafi, Shahram; Tajik, Fouad; Akram, Mojtaba
Abstract: Abadan date palm plantations have long been irrigated by rivers under the tidal effects of the Persian Gulf. During high tides, river water makes subirrigation possible while during low tides the same ditches drain out the plant root zone. Recently parts of the plantation have been under traditional drainage and surprisingly failed to work efficiently. In order to find the cause, the hydraulic conductivity of the soil layers was measured using parallel drains which show that the topsoil up to 70 cm is very permeable, but then up to 95 cm it is impermeable. Piezometric measurements also show that the soil between 70 and 130 cm is impermeable. The ratio of contribution (RC) of the soil layers to the total flow in the soil profile decreases with depth. Values of the RC for the first 60 and 70 cm soil depths are about 91 and 98% respectively. Although soil texture in the first layer has been classified as clay, biological activities, mostly live roots, have changed both the magnitude and size of the pores. It was concluded that in tidal subirrigation, only the upper part of the soil which has been under the root spread can be assumed to be permeable. Copyright © 2018 John Wiley & Sons, Ltd.